MENGKAJI FENOMENA PERNIKAHAN SEDARAH BERDASARKAN PANDANGAN HUKUM ISLAM, UNDANG- UNDANG DAN SAINS (ILMU KESEHATAN) - Rohman Muzadi; Surya Adi Jaya; Yosie Nurwida Sari (JOURNAL OF LAW AND NATION, 2023)
Cousin marriage is a marriage that occurs between a man and a woman who still have very close blood relations in their family lineage, whether through legitimate or illegitimate birth, or through marriage, even involving siblings, whether legitimate or illegitimate. This type of marriage is considered taboo in most societies. Furthermore, it is prohibited from a religious, legal, and scientific (health) perspective. The prohibition is not without reason, as cousin marriage is known to pose various health risks, especially for their offspring. The prohibition of cousin marriage is stipulated in the Marriage Law, Article 8, Number 1 of 1974, as well as in the Quran, Surah An-Nisa, Verse 23, and is supported by data and research in the field of health.